Absence of Placental Transfer of Pentasaccharide (Fondaparinux, Arixtra®) in the Dually Perfused Human Cotyledon in vitro - Lagrange, F.; Vergnes, C.; Brun, J.L.; Paolucci, F.; Nadal, T.; Leng, J.J.; Saux, M.C.; Banwarth, B. (Thrombosis and Haemostasis, 2002)
The synthetic pentasaccharide, fondaparinux, is the first of a new antithrombotic class: selective factor Xa inhibitors. Comparative clinical trials of fondaparinux versus heparins in prevention and treatment of venous thromboembolism are ongoing. Little is known about fondaparinux during pregnancy, as women of child-bearing potential were excluded from clinical trials. No particular safety issue, for either mother or fetus, has been reported for heparins. The objective of this study was to compare in vitro the steady state placental transfer of fondaparinux and enoxaparin at the plasma concentrations reached during acute treatment of venous thromboembolism (1.75 µg/mL and 1 anti- Xa IU/mL respectively), using antipyrine (20 mg/L) as reference. No biological activity was detectable in the fetal venous effluent during perfusion of enoxaparin-antipyrine, fondaparinux-antipyrine or control media. Furthermore, fetal venous samples did not differ significantly from fetal arterial samples. This apparent absence of placental transfer supports further evaluation of fondaparinux in pregnant women.
Keywords: Thromboembolism; pregnancy; pentasaccharide; fondaparinux; enoxaparin; placental transfer